2003
DOI: 10.1046/j.1365-2133.2003.05033.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of photodynamic therapy with topical 5-fluorouracil in Bowen's disease

Abstract: Topical ALA-PDT is more effective than topical 5-FU in the treatment of BD, with fewer adverse events. ALA-PDT should be considered one of the first-line therapeutic options for BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
203
1
7

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(219 citation statements)
references
References 18 publications
8
203
1
7
Order By: Relevance
“…73 In this trial, MAL-PDT was found to be superior to 5FU and cryosurgery in both efficacy and cosmesis, 73 a finding corroborated by others. 71,72 Unfortunately, PDT has shown very poor efficacy in managing invasive SCC. 74 Given the poor healing of SCC in situ lesions of the lower leg in response to more established therapies, PDT may be a logical option in such cases.…”
Section: Photodynamic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…73 In this trial, MAL-PDT was found to be superior to 5FU and cryosurgery in both efficacy and cosmesis, 73 a finding corroborated by others. 71,72 Unfortunately, PDT has shown very poor efficacy in managing invasive SCC. 74 Given the poor healing of SCC in situ lesions of the lower leg in response to more established therapies, PDT may be a logical option in such cases.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…69 A number of studies have highlighted the effectiveness of 1 to 2 ALA-PDT treatment sessions in treating SCC in situ, with complete response at 12 months ranging from 80% to 100%. [70][71][72] ALA-PDT has shown particular efficacy in treating SCC in situ located on the lower leg, 71 a region of poor healing with other therapies. In a large randomized controlled trial that included 225 SCC in situ patients, MAL-PDT produced an 80% complete response rate by 12 months of follow-up, along with a good or excellent cosmetic outcome in 97% of cases.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Os estudos mostram excelente resultados cosméticos entre 91% e 98% dos pacientes tratados. 22,28,39,40 Em relação à doença de Bowen (DB), os estudos conduzidos com ALA (em geral ALA 20% em formulação com creme e com fontes de luz variáveis) mostram índices de cura de 88% a 100%. 28,[39][40][41] No maior estudo multicêntrico conduzido por Morton e cols, o índice de cura inicial foi de 93%.…”
Section: Aplicações Clínicas Oncológicas Em Dermatologiaunclassified
“…ALA combined with red light has significantly better results than the ones obtained with 5-fluorouracil or cryotherapy at 12 months follow-up with good or excellent cosmetic outcome (Morton et al, 2002). Comparing the effects of 20% ALA-PDT and fluorouracil therapy, a bicentric randomized trial showed a complete response in 88% of the lesions treated with ALA-PDT and only 67% after treatment with fluorouracil (Salim et al, 2003). However, literature data regarding the effect of PDT in Bowen's disease are controversial, some researchers reporting positive results in 90-100%, while others only in 50% of the cases (Fijan et al, 1995).…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%